Solitary fibrous tumor of the ilium: A case report. Issue 51 (December 2017) - Ge, Xiuhong; Liao, Jinsheng; Choo, Ryan Justin; Yan, Juncheng; Zhang, Jingfeng
Abstract: Rationale: Solitary fibrous tumors (SFTs) are rare spindle cell tumors that are most commonly found in the mediastinal pleura. Although there are increasingly more reports of extra-pleural SFTs, reports of SFTs in bone are very rare. To our knowledge, a SFT of the ilium has not yet been reported. With low specificity on computer tomograpy and magnetic resonance imaging, SFTs are easily misdiagnosed. Patient concerns: A 33-year-old man visited our hospital due to repeated right ilium pain for 3 months. The pain was dull and bearable, with no hip joint dyskinesia. The relevant physical examinations are negative. The patient was healthy before and had a negative family history. Radiologically, a large mass with inhomogeneous attenuation and intensity and obvious heterogeneous enhancement was misdiagnosed as a giant cell tumor of ilium. Diagnoses: The man was diagnosed as the solitary fibrous tumor of right ilium. Interventions: The patient was performed an "incision biopsy of the right ilium" and "extended resection of tumor". Outcomes: The pathology and immunohistochemistry was confirmed as the solitary fibrous tumors. The patient was followed-up by computed tomography of pelvis in local hospital every 6 mouths, and there is no recurrence and any symptoms. Lessons: We learned that the solitary fibrous tumor could locate in the ilium, and when we see imaging manifestations like this case, we should think it may be SFT.